Effects of media type on Shiga toxigenic E. coli growth patterns - Nicholas W. Baumann; Nicholas J. Sevart; Minto Michael; Donka T. Milke; G. Lewis; R. Moxley; Randall K. Phebus (Kansas Agricultural Experiment Station Research Reports, 2014)
Escherichia coli O157:H7 was declared to be an adulterant in raw ground beef in 1994 by the United States Department of Agriculture Food Safety and Inspection Service following a large and deadly foodborne disease outbreak in the Pacific Northwest involving undercooked hamburgers sold at Jack-in-the-Box restaurants. Due to their recognition as significant human foodborne pathogens, six additional strains (serotypes) of Shiga toxin-producing E. coli (STEC) were also deemed to be adulterants in raw beef products in 2012. The beef processing industry has worked diligently since the mid-1990s to control the presence of E. coli O157:H7 in finished raw products through the implementation of aggressive microbial testing programs and the incorporation of antimicrobial intervention technologies validated to substantially reduce the presence of this pathogenic organism. This effort has occurred within the framework of Hazard Analysis and Critical Control Points (HACCP) programs. With the addition of six additional STEC strains that also must be controlled through these programs, laboratory-testing methods must be developed and implemented to afford the industry a means to accurately document their control programs. Shiga toxin-producing E. coli cultivation, identification, and quantification methods are currently lacking. Establishing behavior patterns for these STECs will allow the beef processing industry to better develop methods for controlling or eliminating them in the food supply. To accomplish this, the prevalence of these organisms must first be established through sampling, but research into which media type is best for enriching samples to recover and identify all STEC organisms has been limited. To determine which media type was best suited for recovery of STECs, we inoculated multiple enrichment media types with the target strains and observed their growth patterns.
Keywords: Cattlemen' s Day; 2014; Kansas Agricultural Experiment Station contribution; no. 14-262-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1101; Beef Cattle Research; 2014 is known as Cattlemen' s Day; Beef; Shiga toxin-producing E. coli; Media types